OPTIMIZATION OF THE NUMBER OF CLUSTERS ON K-MEDOIDS USING CHEBYCHEV AND MANHATTAN ON GOLD SELLING GROUPING - Dedi Triyanto; Deny Kurniawan; Mochamad Wahyudi (Jurnal Mantik, 2022)
Gold is a type of precious metal that can maintain value and can be used for exchange. Gold has attractive properties, so many people like to buy gold for jewelry and also for investments that can be resold when they need money quickly. During the COVID-19 pandemic, some sales sectors experienced a decline but gold was still selling well. M. Siregar Gold Shop serves gold jewelry sales. Gold jewelery sales transactions at the M. Siregar gold shop are stored in the database. Every day the transaction data is increasing, so the data is getting more and more. From the mountains of data we can dig up information or generate knowledge. M. Siregar's gold shop has difficulty in knowing the type of gold that is selling well, making it difficult for gold shop owners to determine the right gold supply. This study aims to classify gold sales at the M. Sisregar gold shop so that it is known which types of gold are selling well. This grouping uses the K-Medoids method with the calculation of the distance between the Chebychec distance and the Manhanttan distance. The data is taken from the sales of gold at the M. Siregar store from November 2021 to March 2022. To produce an optimal grouping, this grouping is tested with several number of clusters by calculating the distance between Chebycev distance and Manhattan distance by calculating the DBI value of each number of clusters. . The result of the optimal grouping of gold sales is the K-Medoids method with the calculation of the Chebycev distance with the number of clusters = 2 with DBI value = 0.024.ns.